KAJIAN PEMANFAATAN BIOMASSA LIMBAH INDUSTRI MINYAK PICUNG (Pangium Edule Reinw) UNTUK BIOBRIKET SUMBER ENERGI ALTERNATIF DI DESA PULAU PICUNG, KAMPAR - Akhyar Ali; Dewi Fortuna Ayu; Fajar Restuhadi (Jurnal Sagu, 2012)
Seed of picung (Pangium edule Reinw) contains 70 % kernel (weight) and 40 % husk (weight). Itsnucleus’s seeds contain 21-27 % oils that can be extracted. More than its 70 % component is an oil cake.The huge amount of oil cake can be used as a solid fuel such as Biomass Briket (Baiobriket). Biobriket hasweight 23,046 gram,long 3,469 cm, wide 2,804 cm and high 2,277 cm. Biobriket picung is produced bymanual process inlet dry materials that is pushed and pressed by hydroulic press. The pressing processproduces solid materials that will be piece into specific size. Picung oil cakes have a weakness as a solidfuel. It has no high heating value and its physic characteristic that has low binder. To increasing heatingvalue, glycerol is added. Because glycerol has a heating value equal to 1353 kcal/ kg. Glycerol can beused as an alternative heating resource. Binding problems can be solved by adding tapioca. Optimumadding of tapioca is not more than 5%. The final step of this research is found the comparison of qualitybetween optimal biobriket picung oil cake. This research used central composit design. The first factorwas quantity of glycerol (X1) and the second factor was quantity of tapioca (X2). Picung oil cake usedwas 200 gram. First factor’s range was between 1 – 5,5 % weight of oil seed or at 1,76-9,69 ml (densityglycerol was 1,13 g/ml). The seconds factor range was 1 – 5 % weight of oil cake or at 2-10 gram.Optimation response used was heating value (Y). Analysis with response surface method shows thataddition of glycerol had a positive influence to the heating value of biobriket with desirability 94 %. Theoptimum value for heating calor biobriket was 6243,62 kcal/kg.